Use of Carbon Fibre Composite Molecular Sieves for Air Separation - Timothy D. Burchell; Omats O. Omatete; Nidia C. Gallego; Frederick S. Baker (Adsorption Science & Technology)
The adsorption of oxygen, nitrogen and carbon dioxide onto a carbon fibre composite was investigated using static and dynamic techniques. Molecular-sieving effects in the composite were highlighted by the adsorption of carbon dioxide, a more sensitive probe molecule for the presence of micro-porosity in adsorbents. The kinetic studies revealed that oxygen was more rapidly adsorbed on the composite than nitrogen and with a higher uptake under equilibrium conditions. Preliminary experiments indicated that the carbon fibre composite was capable of separating oxygen and nitrogen from air on the basis of the different diffusion rates of the two molecules in the micropore network of the composite. It is proposed that the relatively high electrical conductivity of the carbon fibre composite material could be exploited for air separation by facilitating the production of O 2 and N 2 through electrical swing adsorption rather than the depressurization of adsorber beds.